Analisis Inbound Marketing Umkm Dalam Meningkatkan Brand Awaresness: Studi Strategy Branding Pada Sablon Rainbow Creative Sangatta Kutai Timur - Amir Machmud; Mohammad Kresna Noer (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Although Sangatta has experienced expansion for more than two decades into East Kutai Regency, the development of MSMEs is still in the developing stage, one of the MSMEs that has developed is Sablon Rainbow Creative Sangatta and is the first screen printing company to be established. Screen printing customers still place orders outside East Kutai or outside the island. This study aims to analyze the branding marketing strategy of Sablon Rainbow Creative Sangatta in increasing customers for Sablon Rainbow Creative Sangatta. This study uses a descriptive qualitative approach. The data collection method used is in-depth interviews with several informants, namely the owner of Sablon Rainbow, regular customers and one of the brand experts. The data obtained is then processed based on the principles of attract, convert, close and delight. The results of the study show that MSME Rainbow Creative has high Brand Awareness and has implemented inbound marketing.